2017
DOI: 10.1016/j.joca.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Unique spatiotemporal and dynamic gait compensations in the rat monoiodoacetate injection and medial meniscus transection models of knee osteoarthritis

Abstract: Objective In rodent osteoarthritis models, behavioral changes are often subtle and require highly sensitive methods to detect these changes. Gait analysis is one assay that may provide sensitive, quantitative measurement of these behavioral changes1. To increase detection sensitivity of gait assessments relative to spatiotemporal gait collection alone, we combined our spatiotemporal and dynamic gait collection systems. Using this combined system, gait was assessed in the rat medial meniscus transection model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…Joint surfaces present many deep cracks and a very marked hypocellularity with cells having a very condensed appearance (arrows). (2020) 10:5277 | https://doi.org/10.1038/s41598-020-62146-0 www.nature.com/scientificreports www.nature.com/scientificreports/ In accordance with several previous studies [50][51][52][53] , we observed that MIA injection induced severe cartilage damage demonstrating that this method was effective to induce severe OA. Thus, as in human clinical cases, our rat model is suitable for total knee arthroplasty.…”
Section: Discussionsupporting
confidence: 90%
“…Joint surfaces present many deep cracks and a very marked hypocellularity with cells having a very condensed appearance (arrows). (2020) 10:5277 | https://doi.org/10.1038/s41598-020-62146-0 www.nature.com/scientificreports www.nature.com/scientificreports/ In accordance with several previous studies [50][51][52][53] , we observed that MIA injection induced severe cartilage damage demonstrating that this method was effective to induce severe OA. Thus, as in human clinical cases, our rat model is suitable for total knee arthroplasty.…”
Section: Discussionsupporting
confidence: 90%
“…This schematic shows a side view of EDGAR (A), floor design with instrumentation panels (B), and a single frame from a representative trial video (C). Image from Jacobs et al 58 .…”
Section: Resultsmentioning
confidence: 99%
“…This study points to the use of T1rho and T2 as noninvasive tools, which are sensitive to early changes in cartilage composition following meniscus injury. Jacobs et al 58 assessed differences in gait profiles of rats with medial meniscus transection (MMT) and monoiodoacetate (MIA) injection to simulate OA. The combined analysis of dynamic gait data with spatiotemporal data increased the sensitivity of detecting differences between the two OA models (Fig.…”
Section: Meniscus Injury and Oa Developmentmentioning
confidence: 99%
“…associated hardware and open-source analysis software were used to acquire spatiotemporal gait data [17,23,24] (additional information available online 1 ). Briefly, the arena is an enclosed, Fig.…”
Section: Spatiotemporal Gait Testing a Custom-built Gait Arena Withmentioning
confidence: 99%
“…Similar to grip strength, gait analysis has been used previously to quantify functional changes in rodent models of a variety of injury conditions including knee instability and osteoarthritis [15][16][17], patellar tendon degeneration [18], Achilles tendon injury [19], rotator cuff damage [20], and spinal cord injury [21]. Additionally, a recent study evaluated gait changes due to elbow contracture in a murine model [22]; however, in this study animals were only evaluated at a single time point for a single gait parameter.…”
Section: Introductionmentioning
confidence: 99%